Peran Pembimbing Kemasyarakatan dalam Pembimbingan Klien Lansia di Balai Pemasyarakatan Kelas II Pati - Aji Darma Agus Awibowo; Iskandar Wibawa (LPPM Universitas Ekasakti Padang, 2023)
Guidance is one of the tasks of social counselors with the aim that correctional clients become better human beings and not repeat their actions again, the implementation of mentoring for elderly clients certainly cannot be equated with the implementation of counseling for children and adult clients. This study aims to determine the role of social counselors of Bapas Class II Pati in carrying out guidance and supervision of elderly clients. This research was conducted with the main subject being the implementation of mentoring carried out by the social counselor of the Batch Class II Pati. The method used in this study is empirical juridical with data sources used by researchers are primary data supported by secondary data sources. Primary data collection techniques obtained through interviews and observation, and for secondary data obtained from the results of literature studies. Data analysis used by researchers using qualitative data analysis techniques. Based on the results of the research and discussion that has been carried out, it is clear that the Bapas Pati Community Counselor has carried out effective mentoring even though the implementation is constrained by a large work area. So that some elderly clients find it difficult to carry out the obligation to report every month.